Alkali‐Metal Mediation: Diversity of Applications in Main‐Group Organometallic Chemistry. Issue 17 (3rd December 2020) - Gentner, Thomas X.; Mulvey, Robert E.
Abstract: Organolithium compounds have been at the forefront of synthetic chemistry for over a century, as they mediate the synthesis of myriads of compounds that are utilised worldwide in academic and industrial settings. For that reason, lithium has always been the most important alkali metal in organometallic chemistry. Today, that importance is being seriously challenged by sodium and potassium, as the alkali‐metal mediation of organic reactions in general has started branching off in several new directions. Recent examples covering main‐group homogeneous catalysis, stoichiometric organic synthesis, low‐valent main‐group metal chemistry, polymerization, and green chemistry are showcased in this Review. Since alkali‐metal compounds are often not the end products of these applications, their roles are rarely given top billing. Thus, this Review has been written to alert the community to this rising unifying phenomenon of "alkali‐metal mediation". Abstract : Alkali metals top the league when it comes to mediating reactions. Organolithium compounds have long been their captain, but now organosodium and organopotassium compounds are finding their form too. This Review highlights their victories in homogeneous catalysis, organic synthesis, low‐valent aluminium chemistry, polymerization, and green chemistry.